156k views
5 votes
Prove that

(1 + cot A + tan A) (sin A - cos A) = sin A tan A - cot A cos A

User Tempy
by
5.5k points

1 Answer

1 vote

Answer:

see explanation

Explanation:

Using the trigonometric identities

tan A =
(sinA)/(cosA) , cot A =
(cosA)/(sinA)

Consider the left side

(1 + cotA + tanA)(sinA - cosA)

each term in the second factor is multiplied by each term in the first factor.

1(sinA - cosA) + cotA(sinA - cosA) + tanA(sinA - cosA)

= sinA - cosA + cosA -
(cos^2A)/(sinA) +
(sin^2A)/(cosA) - sinA ( collect like terms )

=
(sin^2A)/(cosA) -
(cos^2A)/(sinA)

= ( sinA ×
(sinA)/(cosA) ) - (
(cosA)/(sinA) × cosA )

= sinAtanA - cotAcosA

= right side ⇒ proven

User Talves
by
6.0k points